STEM education: the career counselor's roles and responsibilities - Zainudin, Zaida Nor; Syed Abdullah, Sharifah Intan Sharina; Mohamad Yusop, Yusni; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2019)
Some countries have adopted STEM policies in their education. Many policies, initiatives, training and funds are for STEM development aimed at expanding science, technology, engineering, and mathematical workforce. This education investment also aims to create a larger, more diverse group of talent pursuing technical careers. Counselors are among those who should actively involve in supporting and promoting STEM Education in school. This paper is to see the roles can be played by counselors. This qualitative research involves 59 school counselors in Selangor, Malaysia. Research data was analyzed using nested analysis approach. The analysis is considered as nested in a way that it combines descriptive quantitative analysis with an in-depth thematic qualitative analysis. Thematic coding is applied in gathering the themes. Six themes emerged from the data. The themes are counselor must be (a) well-versed in STEM, (b) giving information and understanding of STEM to students, (c) instill students’ interest, (d) knowledgeable of stem career prospects, (e) knowledgeable in career psychometrics tests, and (f) be prepared with students’ personal issues. We conclude that the role of a counselor in school is extremely important to support and promote STEM Education.